Relación entre la calidad de sueño y somnolencia en estudiantes de un centro preuniversitario estatal, Trujillo - Mendoza Céspedes, Héctor Jean Pier (2022)
Evaluate the relationship between sleep quality and sleepiness in students of a state pre-university center, Trujillo. MATERIAL AND METHODS: An analytical cross-sectional study was conducted on a random sample of 759 students from the Pre-University Study Center of the National University of Trujillo who responded to the Pittsburgh Sleep Quality Index (PSQI) and the Epworth Sleepiness Scale (ESS). In addition, sociodemographic variables were included. The Chi-square test was applied to determine the relationship between the variables (IC: 95%). RESULTS: In the students evaluated, the median age was 17 (17; 18) years and 51% were male. Likewise, 84% had poor sleep quality (ICSP ≥5). The levels of daytime sleepiness were 54% in the low category, 22% intermediate and 22% excessive. Combining the variables, it was found that 43% of the students who had poor quality of sleep presented low daytime sleepiness, 1% of the students who had good quality of sleep presented excessive daytime sleepiness. Applying (X²=47.731; CI:95%) [p<0.01]. CONCLUSION: The quality of sleep presents a significant relationship to the levels of daytime sleepiness of pre-university students.